Preparation method of anode-supported solid oxide fuel cell half-cell anode strip
The anode-supported solid oxide fuel cell half-cell anode sheet is prepared through the co-casting-warm isostatic pressing process, which solves the problems of high preparation cost, complicated process and poor battery performance in the existing technology, and achieves higher flatness. strength, mechanical strength and preparation efficiency.
Patent Information
- Application Number
- CN202411874893.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, when preparing a flat-type anode-supported solid oxide fuel cell, there are problems such as high production costs, complex processes, low sintering and molding rate of the half-cell and battery performance.
A co-casting-warm isostatic pressing process is used to prepare an anode membrane strip through one-time casting, and a co-casting method is used to prepare an electrolyte membrane strip on its surface, followed by compression molding and sintering to obtain an anode-supported solid oxide fuel. Battery half cell anode plate.
Improved the fit between the anode layer and the electrolyte layer, optimized the half-cell preparation process, made the solid oxide fuel cell half-cell anode sheet have higher flatness and mechanical strength, reduced production costs, and improved battery preparation efficiency.
Smart Images

Figure CN119340406A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of fuel cells, and in particular to a method for preparing an anode sheet of an anode-supported solid oxide fuel cell half cell. Background Art
[0002] Fuel cells are a new type of power generation technology with many advantages such as high efficiency, cleanliness, safety and reliability. In addition to the common advantages of fuel cells such as high efficiency and environmental friendliness, solid oxide fuel cells (SOFCs) are more flexible in design, more convenient to operate, and safer and more reliable due to their all-solid-state characteristics.
[0003] A flat-plate anode-supported solid oxide fuel cell is a type of solid oxide fuel cell. At present, the preparation of a flat-plate anode-supported solid oxide fuel cell is mainly to prepare a support green body by tape casting, then press the sheets together by hot pressing, and then use electrolyte slurry to tape cast an electrolyte green body, and then stack and laminate it with the anode support, and then sinter it into a half-cell, and finally print the isolation layer, sinter and print the cathode, and sinter to prepare a full cell, or directly print the cathode and sinter to prepare a full cell.
[0004] However, the batteries prepared by this method have the problems of high production cost and complicated process. In addition, the support and electrolyte have different casting formulas. The two are not well combined under hot pressing lamination conditions, which will lead to the introduction of impurities and stratification, resulting in low battery sintering rate and affecting battery performance. At the same time, the thickness of the electrolyte layer is required to be thin, which is difficult to control. Uneven thickness or excessive thickness will affect battery performance. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide a method for preparing an anode sheet of a half-cell of a solid oxide fuel cell supported by an anode in view of the above-mentioned deficiencies of the prior art. The method adopts a co-casting-warm isostatic pressing process to prepare a solid oxide fuel cell, and by optimizing the preparation process of the half-cell, the solid oxide fuel cell half-cell anode sheet has higher flatness and mechanical strength, and solves the problem of insufficient flatness of the cell caused by inconsistent shrinkage between layers during the firing process of the half-cell.
[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing an anode sheet of an anode-supported solid oxide fuel cell half cell, characterized in that the method comprises the following steps: Step 1, preparing an anode film strip: at room temperature, ethanol and butanone are prepared into a mixed solvent, and then nickel oxide, 3YSZ, corn starch, triethanolamine, polyethylene glycol, polyvinyl butyral ester, and dioctyl phthalate are added to the mixed solvent in sequence, and a stable and uniform anode slurry is formed by ball milling, and then the anode slurry is filtered and degassed, and an anode film strip with uniform thickness is prepared by a one-time casting method; Step 2, preparing an electrolyte layer membrane tape: at room temperature, taking 8YSZ, triethanolamine, polyethylene glycol, polyvinyl butyral ester, and dioctyl phthalate, sequentially adding them into an ethanol solvent, forming a stable and uniform electrolyte slurry by ball milling, and then filtering and degassing the electrolyte slurry, and preparing an electrolyte membrane tape on the anode membrane tape prepared in step 1 by a co-casting method to obtain a co-cast membrane tape; Step 3, cutting the co-cast film strip obtained in step 3 into blocks, evacuating the blocks and placing them in a warm isostatic press for compression molding to obtain anode green sheets; Step 4: Place the anode green body obtained in step 3 into a high-temperature sintering and binder removal furnace for sintering to obtain an anode-supported solid oxide fuel cell half-cell anode sheet.
[0007] The above-mentioned method for preparing an anode-supported solid oxide fuel cell half-cell anode sheet is characterized in that the volume ratio of ethanol to butanone in the mixed solvent described in step one is 8~10:1~3, the mass ratio of the added materials including nickel oxide, 3YSZ, corn starch, triethanolamine, polyethylene glycol, polyvinyl butyral ester, and dioctyl phthalate is 10~15:10~15:1~2:1~2:1~2:1~2:1~2, and the mass ratio of the mixed solvent to the added materials is 1~2:2~3; the ball milling speed described in step one is 300r / min~600r / min, and the ball milling time is 5h~10h.
[0008] The above-mentioned method for preparing an anode-supported solid oxide fuel cell half-cell anode sheet is characterized in that the degassing time in step one is 20min~40min, the one-time casting method is to spread the degassed anode slurry by casting and drying it at 60℃~100℃ for 3h~12h, and the thickness of the anode film strip is 400μm~500μm.
[0009] The above-mentioned method for preparing an anode-supported solid oxide fuel cell half-cell anode sheet is characterized in that the added materials in step 2 include 8YSZ, triethanolamine, polyethylene glycol, polyvinyl butyral ester, and dioctyl phthalate in a mass ratio of 10~12:0.5~1:0.5~1:0.1~1:0.5~1, and the mass ratio of ethanol solvent to the added materials is 1~2:2~3; the ball milling speed in step 2 is 300r / min~600r / min, and the ball milling time is 3h~5h.
[0010] The above-mentioned method for preparing an anode-supported solid oxide fuel cell half-cell anode sheet is characterized in that the degassing time in step 2 is 30min~60min, the co-casting method is to spread the degassed electrolyte slurry and then dry it at 40℃~80℃ for 1h~5h, the thickness of the electrolyte membrane tape is 10μm~30μm, and the thickness of the co-casting membrane tape is 410μm~530μm.
[0011] The above-mentioned method for preparing an anode-supported solid oxide fuel cell half-cell anode sheet is characterized in that the heating temperature for the pressing molding in step three is 30°C~50°C, the pressure is 10MPa~35MPa, and the holding time is 3min~15min.
[0012] The above-mentioned method for preparing an anode-supported solid oxide fuel cell half-cell anode sheet is characterized in that the sintering process described in step four is: first, the temperature is increased from room temperature to 600°C~1000°C at a rate of 0.5°C / min~2°C / min and kept warm for 4h~12h, and then the temperature is continued to be increased to 1200°C~1400°C at a rate of 0.5°C / min~2°C / min and kept warm for 4h~12h.
[0013] Compared with the prior art, the present invention has the following advantages: 1. The present invention first adopts a single casting method to prepare an anode film strip as an electrode support, and then adopts a co-casting method to cast on the surface of the anode film strip to prepare an electrolyte membrane strip to obtain a co-cast film strip, and obtains an anode-supported solid oxide fuel cell half-cell anode sheet through press molding and sintering. By adopting the casting method to replace the traditional hot pressing lamination, the fit between the anode layer and the electrolyte layer is improved, and the preparation process of the half-cell is optimized, so that the solid oxide fuel cell half-cell anode sheet has higher flatness and mechanical strength, and solves the problem of insufficient battery flatness caused by inconsistent shrinkage between layers during the firing process of the half-cell.
[0014] 2. The co-casting-warm isostatic pressing process adopted by the present invention is simple and easy to control, which greatly shortens the battery preparation process, reduces production costs, and improves battery preparation efficiency.
[0015] 3. The anode-supported solid oxide fuel cell half-cell anode sheet prepared by the present invention has the characteristics of low production cost, high battery sintering molding rate and good battery performance, and is suitable for transportation, aerospace, power supply in remote areas and other fields.
[0016] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a cross-sectional microstructure diagram of the anode-supported solid oxide fuel cell prepared in Example 3 of the present invention.
[0018] Figure 2 This is the electrochemical impedance spectrum of a full cell assembled from the anode-supported solid oxide fuel cell prepared in Example 3 of the present invention.
[0019] Figure 3 This is a power density performance diagram of a full cell assembled from an anode-supported solid oxide fuel cell prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0020] Example 1 This embodiment includes the following steps: Step 1, preparing an anode film strip: at room temperature, prepare a mixed solvent with ethanol and butanone in a volume ratio of 10:3, then take nickel oxide, 3YSZ, corn starch, triethanolamine, polyethylene glycol, polyvinyl butyral ester, dioctyl phthalate and add them to the mixed solvent in a mass ratio of 12:10:1:1.5:2:1:2 in sequence, and the mass ratio of the mixed solvent to the added materials is 2:3, place it in a ball mill for ball milling to form a stable and uniform anode slurry, the ball milling speed is 300r / min, the ball milling time is 5h, and then the anode slurry is filtered and degassed, the degassed time is 20min, and the degassed anode slurry is rolled out by a one-time casting method and dried at 60°C for 8h to prepare an anode film strip with a thickness of 400μm and uniform thickness; Step 2, prepare the electrolyte layer membrane tape: at room temperature, take 8YSZ, triethanolamine, polyethylene glycol, polyvinyl butyral ester, dioctyl phthalate and add them to the ethanol solvent in the mass ratio of 11:0.8:0.75:0.5:0.8 in sequence, and the mass ratio of ethanol solvent to added materials is 1:3, place in a ball mill for ball milling to form a stable and uniform electrolyte slurry, the ball mill speed is 400r / min, the ball milling time is 3h, and then the electrolyte slurry is filtered and degassed, the degassed time is 60min, and the degassed electrolyte slurry is cast and spread by co-casting method, and then dried at 80℃ for 1h, and an electrolyte membrane tape with a thickness of 30μm is prepared on the anode membrane tape prepared in step 1, and a co-cast membrane tape with a thickness of 530μm is obtained; Step 3, cutting the co-cast film tape obtained in step 3 into blocks, evacuating the blocks and placing them in a warm isostatic press for compression molding, wherein the heating temperature for compression molding is 50° C., the pressure is 35 MPa, and the holding time is 15 min, to obtain an anode green body; Step 4: Place the anode green body obtained in step 3 into a high-temperature sintering and binder removal furnace for sintering. First, heat the temperature from room temperature to 600°C at a rate of 0.5°C / min and keep it for 4 hours. Then, continue to heat it to 1200°C at a rate of 2°C / min and keep it for 12 hours to obtain an anode-supported solid oxide fuel cell half-cell anode sheet.
[0021] Example 2 This embodiment includes the following steps: Step 1, preparing an anode film strip: at room temperature, prepare ethanol and butanone into a mixed solvent in a volume ratio of 8:1, then take nickel oxide, 3YSZ, corn starch, triethanolamine, polyethylene glycol, polyvinyl butyral ester, dioctyl phthalate and add them to the mixed solvent in a mass ratio of 15:10:1:2:1.5:1.5:1.5 in sequence, and the mass ratio of the mixed solvent to the added materials is 1:2, place it in a ball mill for ball milling to form a stable and uniform anode slurry, the ball milling speed is 600r / min, the ball milling time is 6h, and then the anode slurry is filtered and degassed, the degassed time is 30min, and the degassed anode slurry is rolled out by a one-time casting method and dried at 80°C for 10h to prepare an anode film strip with a thickness of 450μm and uniform thickness; Step 2, prepare the electrolyte layer membrane tape: at room temperature, take 8YSZ, triethanolamine, polyethylene glycol, polyvinyl butyral ester, dioctyl phthalate and add them to the ethanol solvent in a mass ratio of 11:1:1:1.5:0.8 in sequence, and the mass ratio of ethanol solvent to added materials is 2:3, place in a ball mill for ball milling to form a stable and uniform electrolyte slurry, the ball mill speed is 500r / min, the ball milling time is 4h, and then the electrolyte slurry is filtered and degassed, the degassed time is 40min, and the degassed electrolyte slurry is cast and spread by co-casting method, and then dried at 50°C for 3h, and an electrolyte membrane tape with a thickness of 20μm is prepared on the anode membrane tape prepared in step 1, and a co-cast membrane tape with a thickness of 480μm is obtained; Step 3, cutting the co-cast film tape obtained in step 3 into blocks, evacuating the blocks and placing them in a warm isostatic press for compression molding, wherein the heating temperature for compression molding is 45° C., the pressure is 10 MPa, and the holding time is 15 min, to obtain an anode green body; Step 4: Place the anode green body obtained in step 3 into a high-temperature sintering and debinding furnace for sintering. First, heat the temperature from room temperature to 1000°C at a rate of 1°C / min and keep it for 8 hours. Then, continue to heat it to 1400°C at a rate of 1°C / min and keep it for 6 hours to obtain an anode-supported solid oxide fuel cell half-cell anode sheet.
[0022] Example 3 This embodiment includes the following steps: Step 1, preparing an anode film strip: at room temperature, prepare a mixed solvent with ethanol and butanone in a volume ratio of 9:2, then take nickel oxide, 3YSZ, corn starch, triethanolamine, polyethylene glycol, polyvinyl butyral ester, dioctyl phthalate and add them to the mixed solvent in a mass ratio of 14:13:1.5:1:2:2:1 in sequence, and the mass ratio of the mixed solvent to the added materials is 1:1, place it in a ball mill for ball milling to form a stable and uniform anode slurry, the ball milling speed is 400r / min, the ball milling time is 6h, and then the anode slurry is filtered and degassed, the degassed time is 25min, and the degassed anode slurry is rolled out by a one-time casting method and dried at 100°C for 5h to prepare an anode film strip with a thickness of 450μm and uniform thickness; Step 2, prepare the electrolyte layer membrane tape: at room temperature, take 8YSZ, triethanolamine, polyethylene glycol, polyvinyl butyral ester, dioctyl phthalate and add them to the ethanol solvent in a mass ratio of 11:0.8:0.8:0.2:0.6 in sequence, and the mass ratio of ethanol solvent to added materials is 1:2, place in a ball mill for ball milling to form a stable and uniform electrolyte slurry, the ball mill speed is 400r / min, the ball milling time is 4h, and then the electrolyte slurry is filtered and degassed, the degassed time is 60min, and the degassed electrolyte slurry is cast and spread by co-casting method, and then dried at 80℃ for 5h, and an electrolyte membrane tape with a thickness of 30μm is prepared on the anode membrane tape prepared in step 1, and a co-cast membrane tape with a thickness of 530μm is obtained; Step 3, cutting the co-cast film tape obtained in step 3 into blocks, evacuating the blocks and placing them in a warm isostatic press for compression molding, wherein the heating temperature for compression molding is 50° C., the pressure is 35 MPa, and the holding time is 5 min, to obtain an anode green body; Step 4: Place the anode green body obtained in step 3 into a high-temperature sintering and debinding furnace for sintering. First, heat the temperature from room temperature to 1000°C at a rate of 2°C / min and keep it for 10 hours. Then, continue to heat it to 1300°C at a rate of 1°C / min and keep it for 8 hours to obtain an anode-supported solid oxide fuel cell half-cell anode sheet.
[0023] Figure 1 This is a cross-sectional view of the anode-supported solid oxide fuel cell prepared in this embodiment. Figure 1 It can be seen that the structure of the anode-supported solid oxide fuel cell from top to bottom is an electrolyte layer and an anode support layer.
[0024] Figure 2 The electrochemical impedance spectrum of the full cell assembled from the anode-supported solid oxide fuel cell prepared in this example is shown in FIG. Figure 2 It can be seen that its ohmic resistance is 0.07Ω, which is small, indicating that it has good battery performance.
[0025] Figure 3 The power density performance diagram of the full cell assembled from the anode-supported solid oxide fuel cell prepared in this embodiment is shown in FIG. Figure 3 It can be seen that its power density reaches 1.4W / cm 2 , with good electrochemical performance.
[0026] Example 4 This embodiment includes the following steps: Step 1, preparing an anode film strip: at room temperature, prepare ethanol and butanone in a volume ratio of 5:1 to prepare a mixed solvent, then take nickel oxide, 3YSZ, corn starch, triethanolamine, polyethylene glycol, polyvinyl butyral ester, dioctyl phthalate and add them to the mixed solvent in a mass ratio of 12:13:2:1:1:1.5:1.5 in sequence, and the mass ratio of the mixed solvent to the added materials is 2:3, place it in a ball mill for ball milling to form a stable and uniform anode slurry, the ball milling speed is 600r / min, the ball milling time is 6h, and then the anode slurry is filtered and degassed, the degassed time is 40min, and the degassed anode slurry is rolled out by a one-time casting method and dried at 70°C for 6h to prepare an anode film strip with a thickness of 500μm and uniform thickness; Step 2, prepare the electrolyte layer membrane tape: at room temperature, take 8YSZ, triethanolamine, polyethylene glycol, polyvinyl butyral ester, dioctyl phthalate and add them to the ethanol solvent in a mass ratio of 12:1:1:0.5:0.8 in sequence, and the mass ratio of ethanol solvent to added materials is 2:3, place in a ball mill for ball milling to form a stable and uniform electrolyte slurry, the ball mill speed is 500r / min, the ball milling time is 3.5h, and then the electrolyte slurry is filtered and degassed, the degassed time is 60min, and the degassed electrolyte slurry is cast and spread by co-casting method, and then dried at 50°C for 2h, and an electrolyte membrane tape with a thickness of 30μm is prepared on the anode membrane tape prepared in step 1, and a co-cast membrane tape with a thickness of 500μm is obtained; Step 3, cutting the co-cast film tape obtained in step 3 into blocks, evacuating the blocks and placing them in a warm isostatic press for compression molding, wherein the heating temperature for compression molding is 45° C., the pressure is 25 MPa, and the holding time is 8 min, to obtain an anode green body; Step 4: Place the anode green body obtained in step 3 into a high-temperature sintering and debinding furnace for sintering. First, heat the temperature from room temperature to 900°C at a rate of 1.5°C / min and keep it for 12 hours. Then, continue to heat it to 1350°C at a rate of 1°C / min and keep it for 8 hours to obtain an anode-supported solid oxide fuel cell half-cell anode sheet.
[0027] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A method for preparing an anode sheet of an anode-supported solid oxide fuel cell half cell, characterized in that: The method comprises the following steps: Step 1, preparing an anode film strip: at room temperature, ethanol and butanone are prepared into a mixed solvent, and then nickel oxide, 3YSZ, corn starch, triethanolamine, polyethylene glycol, polyvinyl butyral ester, and dioctyl phthalate are added to the mixed solvent in sequence, and a stable and uniform anode slurry is formed by ball milling, and then the anode slurry is filtered and degassed, and an anode film strip with uniform thickness is prepared by a one-time casting method; Step 2, preparing an electrolyte layer membrane tape: at room temperature, taking 8YSZ, triethanolamine, polyethylene glycol, polyvinyl butyral ester, and dioctyl phthalate, sequentially adding them into an ethanol solvent, forming a stable and uniform electrolyte slurry by ball milling, and then filtering and degassing the electrolyte slurry, and preparing an electrolyte membrane tape on the anode membrane tape prepared in step 1 by a co-casting method to obtain a co-cast membrane tape; Step 3, cutting the co-cast film strip obtained in step 3 into blocks, evacuating the blocks and placing them in a warm isostatic press for compression molding to obtain anode green sheets; Step 4: Place the anode green body obtained in step 3 into a high-temperature sintering and binder removal furnace for sintering to obtain an anode-supported solid oxide fuel cell half-cell anode sheet.
2. The method for preparing an anode sheet of an anode-supported solid oxide fuel cell half cell according to claim 1, characterized in that: The volume ratio of ethanol to butanone in the mixed solvent described in step one is 8-10:1-3, the mass ratio of added materials including nickel oxide, 3YSZ, corn starch, triethanolamine, polyethylene glycol, polyvinyl butyral ester, and dioctyl phthalate is 10-15:10-15:1-2:1-2:1-2:1-2:1-2, and the mass ratio of the mixed solvent to the added materials is 1-2:2-3; the ball milling speed described in step one is 300r / min-600r / min, and the ball milling time is 5h-10h.
3. The method for preparing an anode sheet of an anode-supported solid oxide fuel cell half cell according to claim 1, characterized in that: The degassing time in step one is 20 min to 40 min, the one-time casting method is to spread the degassed anode slurry by casting and then dry it at 60° C. to 100° C. for 3 h to 12 h, and the thickness of the anode film strip is 400 μm to 500 μm.
4. The method for preparing an anode sheet of an anode-supported solid oxide fuel cell half cell according to claim 1, characterized in that: The added materials in step 2 include 8YSZ, triethanolamine, polyethylene glycol, polyvinyl butyral, and dioctyl phthalate in a mass ratio of 10-12:0.5-1:0.5-1:0.1-1:0.5-1, and the mass ratio of ethanol solvent to the added materials is 1-2:2-3; the ball milling speed in step 2 is 300r / min-600r / min, and the ball milling time is 3h-5h.
5. The method for preparing an anode sheet of an anode-supported solid oxide fuel cell half cell according to claim 1, characterized in that: The degassing time in step 2 is 30min~60min, the co-casting method is to spread the degassed electrolyte slurry and then dry it at 40℃~80℃ for 1h~5h, the thickness of the electrolyte membrane tape is 10μm~30μm, and the thickness of the co-cast membrane tape is 410μm~530μm.
6. The method for preparing an anode sheet of an anode-supported solid oxide fuel cell half cell according to claim 1, characterized in that: The heating temperature of the pressing molding in step 3 is 30° C. to 50° C., the pressure is 10 MPa to 35 MPa, and the holding time is 3 min to 15 min.
7. The method for preparing an anode sheet of an anode-supported solid oxide fuel cell half cell according to claim 1, characterized in that: The sintering process in step 4 is: first, the temperature is raised from room temperature to 600°C~1000°C at a rate of 0.5°C / min~2°C / min and kept for 4h~12h, and then the temperature is further raised to 1200°C~1400°C at a rate of 0.5°C / min~2°C / min and kept for 4h~12h.
Citation Information
Patent Citations
NiO-based SOFC (Solid Oxide Fuel Cell) composite anode film material with nano-sheet microcellular structure and preparation method thereof
CN102185148A
Method for preparing anti-carbon composite cathode film material of flat plate type solid oxide fuel cell (SOFC)
CN102364737A
Preparation method for anode support layer of solid oxide fuel cell
CN102394307A
Method for preparing SOFC (Solid Oxide Fuel Cell) anode by adopting spherical and fibrous composite pore forming agent
CN102503531A
Method for manufacturing multilayer thin-film solid oxide fuel cell
CN102593478A
Cited By
Anode self-supporting ultrathin solid oxide electrode and preparation method thereof
CN122552549A